Seroprevalence of IgA and IgM antibodies to Bordetella pertussis in healthy Japanese donors: Assessment for the serological diagnosis of pertussis - Fumimoto, Rei (PLoS One, 2019)
Pertussis is a human respiratory infection caused by the gram-negative bacterium, Bordetella pertussis. To evaluate the pertussis burden and vaccine efficacy, diagnosis and epidemiological surveillance should be based on accurate and valid diagnostic methods. Recently, the serodiagnostic tests Novagnost Bordetella pertussis IgA and IgM were approved in Japan for pertussis diagnostics. Although the anti-pertussis toxin (PT) IgG assay has been used for pertussis diagnosis worldwide, little is known about the anti-B. pertussis IgA and IgM assays. In this study, serum samples from 460 healthy donors were examined to determine the seroprevalence of anti-B. pertussis IgA and IgM in a Japanese population, and its correlation with donor age. Our data demonstrated that anti-B. pertussis IgA and IgM are positively and negatively correlated with age (r = 0.27, r = -0.37; P < 0.001, respectively). Age-specific analysis revealed high titers of anti-B. pertussis IgA in adults (46–50 years), while anti-B. pertussis IgM titers were high in schoolchildren (6–10, 11–15 years). When applying the arbitrary cut-off values for these ages, 17.6% and 39.5% of healthy donors were interpreted as pertussis-positive or indeterminate with anti-B. pertussis IgA (46–50 years) and IgM (11–15 years) titers, respectively. Overall, our findings indicated that the Novagnost Bordetella pertussis IgA and IgM testing could be greatly affected by subject age, limiting its value for pertussis diagnosis.